1983
DOI: 10.1042/bj2120355
|View full text |Cite
|
Sign up to set email alerts
|

Glycoproteins and glycosaminoglycans synthesized by human keratinocytes in culture. Their role in cell-substratum adhesion

Abstract: Glycoproteins and proteoglycans synthesized by human keratinocytes in medium containing D-[1-14C]glucosamine were extracted and analysed by polyacrylamide-gel electrophoresis in the presence of sodium dodecyl sulphate. Extraction of the labelled keratinocytes with 0.5% Triton X-100 removed most of the glycoconjugates and left the cytoskeleton and nuclear residue adherent to the substratum. In addition to the cytoskeletal proteins, there was a relatively simple profile of glycoproteins and glycosaminoglycans as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…HA plays important biological roles in the skin, such as holding moisture, maintaining the architecture and elasticity of tissues, and facilitating the exchange of nutrients and waste products (Laurent and Fraser, 1992;Manuskiatti and Maibach, 1996). HA is synthesized mainly by fibroblasts and keratinocytes, and distributed in the connective tissue of the dermis and the intercellular space of the epidermis (Roberts and Jenner, 1983;Tammi et al, 1988;Sakai et al, 1999). Age-dependent decrease of hyaluronic acid has been identified as one of the major factor responsible for the physical appearance of aged skin, including wrinkle formation and the loss in elasticity of the skin (Longas et al, 1987;Ghersetich et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…HA plays important biological roles in the skin, such as holding moisture, maintaining the architecture and elasticity of tissues, and facilitating the exchange of nutrients and waste products (Laurent and Fraser, 1992;Manuskiatti and Maibach, 1996). HA is synthesized mainly by fibroblasts and keratinocytes, and distributed in the connective tissue of the dermis and the intercellular space of the epidermis (Roberts and Jenner, 1983;Tammi et al, 1988;Sakai et al, 1999). Age-dependent decrease of hyaluronic acid has been identified as one of the major factor responsible for the physical appearance of aged skin, including wrinkle formation and the loss in elasticity of the skin (Longas et al, 1987;Ghersetich et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The basal lamina is a continuous layer of extracellular matrix molecules including type IV collagen, laminin, and entactin. Most basal lamina components have been shown to be epithelial cell products (Briggaman, 1981;Hay, 1981Hay, , 1982Kefalides et al, 1979;Kubo et al, 1984;Martin and Timpl, 1987;Roberts and Jenner, 1983) and are involved in the regulation of epithelial growth and differentiation (Foellmer et al, 1983). The basal keratinocytes adhere to their basal lamina via fine filaments known as anchoring filaments or microfilaments which extend from the hemidesmosomes through the lamina lucida into the lamina densa (see Fig.…”
mentioning
confidence: 99%
“…However, when epidermal cells were cultured in the absence of dermis, the synthesis of hyaluronic acid was considerably reduced, whereas the synthesis of sulfated GAGs was unaffected. Roberts and Jenner (1983) have shown that human keratinocytes when cultured in the presence of 3T3 feeder cells synthesize hyaluronic acid and sulfated GAGs. Similarly, Brown and Parkinson (1983) have demonstrated that human keratinocytes in culture synthesize hyaluronic acid, heparan sulfate, and chondroitin sulfate.…”
mentioning
confidence: 99%